Pengaruh Karakteristik Individu dan Pembelajaran Pegawai terhadap Kinerja Digital Pegawai dengan Mediasi Kapabilitas Dinamis Pegawai (Studi Kasus di Kantor Wilayah Kementerian Agama Provinsi Jawa Tengah) - Andreanus Tejo Suwarno; Indarto Indarto; Djoko Santoso (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of individual characteristics and employee learning on digital performance, with dynamic capabilities as a mediating variable, focusing on financial managers using the SAKTI application at the Regional Office of the Ministry of Religious Affairs in Central Java. This research employs a quantitative approach, utilizing path analysis on a sample of 80 respondents. The results indicate that individual characteristics have a positive and significant effect on digital performance, whereas employee learning does not. Both individual characteristics and employee learning are found to have a positive and significant impact on dynamic capabilities. However, dynamic capabilities do not affect digital performance and fail to mediate the influence of either individual characteristics or employee learning on digital performance. These findings highlight the importance of strengthening individual characteristics and relevant learning to support capability development, even though dynamic capabilities have not been proven to directly enhance digital performance in the context of SAKTI application implementation.   Keywords: Individual Characteristics, Employee Learning, Dynamic Capabilities, Employee Digital Performance